Proposed new design scheme for Legoland Retail Shop at Lot 03-91, 92, 93, 94 & 95, Fifth Floor, Berjaya Times Square, No 1 Jalan Imbi 55100, Kuala Lumpur / Azizah Osman - Osman, Azizah (Faculty of Architecture, Planning and Surveying, 2007)
The purposed of this final project is to realize the design process that involve in the preliminary findings, analysis case study and synthesizing Diploma of Interior Architecture. The suggested title of this project is Proposed New Scheme Design for Legoland Retail Shop at lot 05-91, 92,93,94,95, Fifth Floor, Berjaya Times Square, No.1 Jalan Imbi, 55100, Kuala Lumpur. Before writing this documentation, a lot of procedures has to be met and must follow a systematic process. Various important factors must be considered especially inside the angular space including environment outside the building. The first step before I started this project is to identify constraints and limitations of the existing site, exterior and interior.This is extremely important because, it is aimed to explain what the site problem is and how it can be solve with the project. Research begins from basic design principles up to building roof. Besides that, the research begins of interior space must also be considered as a case study. The nature of the case study directly or indirectly related to the project that I have purposed. Research and data that I have collected are analysis, and lastly synthesized into my design. In fact, a purposed planning was made before I started to proposed new design. Several important aspects must be considered to ensure the space function, such as to fulfill users and comfort. The design made should fulfill the character of users or visitors demand and also match the concepts that need to be shown. By creating this retail shop, it is hoped that it will be able to give benefits to the visitors, society and country.